2014
DOI: 10.2332/allergolint.13-oa-0605
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of a New Therapy Using Rebamipide Eyedrops in Patients with VKC/AKC Refractory to Conventional Anti-Allergic Treatments

Abstract: Our findings suggest that rebamipide eyedrops might attenuate giant papillae in patients with allergic conjunctival diseases and that these eyedrops may be useful for the treatment of not only dry eye but also of allergic conjunctival diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…Similarly, Ueta et al recently in Japan conducted a clinical trial of this drug on 4 patients with VKC/AKC refractory to conventional anti-allergic treatment and observed attenuation of the giant papillae in all 4 patients, thereby, for the first time demonstrating the use of this drug for allergic conjunctival diseases. 16 Reported adverse event rates were null in the study. Maximum benefit among all the patients was found by at least 3-5 weeks of treatment with rebamipide 2%.…”
Section: Discussionmentioning
confidence: 73%
“…Similarly, Ueta et al recently in Japan conducted a clinical trial of this drug on 4 patients with VKC/AKC refractory to conventional anti-allergic treatment and observed attenuation of the giant papillae in all 4 patients, thereby, for the first time demonstrating the use of this drug for allergic conjunctival diseases. 16 Reported adverse event rates were null in the study. Maximum benefit among all the patients was found by at least 3-5 weeks of treatment with rebamipide 2%.…”
Section: Discussionmentioning
confidence: 73%
“…Some patients with allergic conjunctival diseases present with dry eye, which is the type of a decrease in the tear break-up time (BUT) [ 9 , 10 ]. We found that rebamipide suppressed polyI:C-induced inflammatory cytokines in human conjunctival epithelial cells [ 11 ] and suggested that the combination of rebamipide eyedrops and conventional anti-allergic treatments might be effective in patients with vernal/atopic keratoconjunctivitis (VKC, AKC) refractory to conventional treatment with anti-allergic- and/or immunosuppressive/steroid eyedrops [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…The giant papillae associated with vernal keratoconjunctivitis may therefore develop as a result of the interaction of immune cells and conjunctival fibroblasts. Rebamipide eyedrops were recently shown to ameliorate giant papillae in four patients with vernal keratoconjunctivitis or atopic keratoconjunctivitis 25. The mechanism of this therapeutic effect of rebamipide remains unclear, but it is possible that it is due at least in part to suppression of the function of conjunctival fibroblasts.…”
Section: Discussionmentioning
confidence: 99%